PENGARUH MODEL THINK PAIR SHARE (TPS) DAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 3 DAN 5 PANJER TAHUN AJARAN 2016/2017 - Rahmatin, Dwi Ana Indra; Suryandari, Kartika Chrysti; Susiani, Tri Saptuti (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The objectives of this research are to proof effect on the implementation of think pair share (TPS) model and problem based learning (PBL) to students? learning outcome of IPA for fifth grade students. The population of this research is the whole students of SDN 3 and 5 Panjer and SDN Pangebatan in the academic year of 2016/2017, and the sample is fifth grade students using purposive sampling. This research was using quasi experiment by non-equivalent control group design. Technique of collecting data were test to gain students? cognitive and non-test observation, interview, and documentation. Data were analyzed using t-test. The results of this research show that there is the different effect on the implementation of think pair share (TPS) model and problem based learning (PBL) to students? learning outcome of IPA. Using PBL was better than model TPS, based on t-test results show that the significant score is higher than (0,138>0,05) and value is lower than (1,507 < 2, 003). Keywords: learning outcome, model Think Pair Share (TPS), Problem Based Learning (PBL)